Analisis Dan Perbaikan Usability Aplikasi Mobile KAI Access Dengan Metode Usability Testing Dan Use Questionnaire - Kevin Ryan Hadi; Hanifah Muslimah Az-Zahra; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The most important aspect of measuring the quality of applications is usability. Usability can be determines how far a products or service can be used by user for reached the purpose and how easy to use the application interface.Applications with a high usability levels basically will usually have more users and loyal. Otherwise, if the usability levels of applications is too low eventually will be abandoned by the users and switch to the another application. In this study, which application will be analyzed is the mobile application of train ticket booking KAI Access. Measurement usability can be use usability testing techniques where the product evaluation process involves direct testing to the user sample. This test will be doing in three steps, first test assignment, second fill out questionnaire and third interview. Each parameter has several statements will be given to the user to assess the usability level of the KAI Access application. There are two tests in this study, beginning test and finals test. beginning tests were performed to analyze usability levels before recommendation. Then final tests were performed to analyze usability levels after recommendation. The recommendation will be used design guidelines to enhance best result.